Experimental approaches to developing and evaluating novel treatments for TBI and SCI - Dietrich, W. Dalton (Henry Stewart Talks, 2011)
Brain and spinal cord trauma, Epidemiology of the clinical condition, Animal modeling approaches, Pathophysiological mechanisms of CNS injury, Clinically relevant outcome measures, Neuropathology, Behavioral outcomes, Clinical trials, Novel treatments